2020
DOI: 10.7717/peerj.8196
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling in recurrent miscarriage

Abstract: Recurrent miscarriage (RM) is a complex clinical problem. However, specific diagnostic biomarkers and candidate regulatory targets have not yet been identified. To explore RM-related biological markers and processes, we performed a genome-wide DNA methylation analysis using the Illumina Infinium HumanMethylation450 array platform. Methylation variable positions and differentially methylated regions (DMRs) were selected using the Limma package in R language. Thereafter, gene ontology (GO) enrichment analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Ген PRDM16 является импринтированным с экспрессией с отцовского аллеля [30]. Дифференциальное метилирование гена PRDM16 было обнаружено в образцах децидуального эпителия матки, полученного путем выскабливания, у женщин с привычным невынашиванием беременности [31]. Все это указывает на возможное влияние уровня метилирования гена PRDM16 у матери на нормальное развитие потомства.…”
Section: Medical Geneticsunclassified
“…Ген PRDM16 является импринтированным с экспрессией с отцовского аллеля [30]. Дифференциальное метилирование гена PRDM16 было обнаружено в образцах децидуального эпителия матки, полученного путем выскабливания, у женщин с привычным невынашиванием беременности [31]. Все это указывает на возможное влияние уровня метилирования гена PRDM16 у матери на нормальное развитие потомства.…”
Section: Medical Geneticsunclassified
“…Li et al. conducted a genome-wide screening of DNA methylation in decidual samples from women with RPL ( 54 ). The findings showed that the differentially methylated genes ( PRDM16 , HLA-E , HLA-G , and ISG15 ) were closely related to embryonic development ( 55 57 ).…”
Section: Omics Studies Of Decidua In Recurrent Pregnancy Lossmentioning
confidence: 99%
“…Li et al. also verified the upregulated expression of ISG15 in RPL by utilizing RNA-seq technology, and these authors found that ISG15 was involved in the type I interferon signaling pathway by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses ( 54 ). CREB5 regulates cell growth, proliferation, differentiation and the cell cycle and belongs to the cAMP response element ( CRE )-binding protein family ( 58 ).…”
Section: Omics Studies Of Decidua In Recurrent Pregnancy Lossmentioning
confidence: 99%